Peran Pendidik Dalam Menangani Tantrum Anak Usia 4-5 Tahun Dengan Metode Time Out - Sulistiawati, Siti; Putri, Ayu Aprilia Pangestu (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2025)
The Role Of Educators In Handling Tantrum In Children Aged 4-5 Years Using The Time Out Method. This study aims to determine the efforts of educators in handling tantrum children using the time out method. The time out method is a temporary elimination method used by educators to handle tantrum children by separating children from their peers such as the corner of the class so as not to hurt people around them, children calm their emotions and reflect on the actions they do. Tantrums are emotional outbursts experienced by children, marked by changes in angry behavior, rolling around and throwing things. The method used in this study is qualitative or field studies, observation and literature studies, by analyzing the findings from observations in the field and connecting them to theories related to the research study. The problem in this study is based on RA Miftahul Huda which has problems with tantrum children in class A aged 4-5 years. The results of the study explain that the application of the time out method at RA Miftahul Huda is very effective in dealing with tantrum children, children tend to calm down and be quiet more quickly if using the time out method.